Bullous pemphigoid in a patient with a neuropsychological disorder and a possible novel drug trigger: A case report and review of the literature - Sarah M. Dyson; Priya U. Patel; Laszlo Igali; George W. M. Millington (Wiley, 2022)
Abstract A 59‐year‐old woman with schizoaffective disorder presented with an itchy, blistering generalised rash. One month prior, she had started empagliflozin, a sodium glucose transporter‐2 (SGLT‐2) inhibitor, used in type‐2‐diabetes. She was already established on paliperidone, an atypical antipsychotic, for 1 year. Serology at presentation was positive for anti‐pemphigoid antibodies. Histology demonstrated subepidermal blistering, perivascular inflammation and eosinophils. Direct immunofluorescence was characteristic of bullous pemphigoid (BP), with linear IgG and C3 at the basement membrane. Both empagliflozin and paliperidone were discontinued. However, the blisters persisted. Treatment included: topical Dermovate and Eumovate ointment for the body and face respectively, alongside oral doxycycline 200 mg and prednisolone 40 mg for a week (reducing by 5 mg/week over 8 weeks). Nevertheless, new blisters continued developing, hence dapsone 50 mg was introduced, with significant improvement. Increasingly, several neurological and psychiatric disorders have been linked with BP, complicating aetiology and management. The underlying mechanism for these associations is not fully understood. Bullous pemphigoid autoantigens BP180 and BP230 are expressed in the central nervous system and it is thought that neurodegeneration may expose antigens to the immune system, generating a cross‐reactive immune response. However, there also appears to be bidirectional causality between BP and neuropsychological conditions. Furthermore, as there was an association of empagliflozin initiation and BP onset, this further complicates the aetiology and presents a potential novel drug cause of BP. This case emphasises the neuropsychological issues associated with managing complex BP cases, a possible novel cause of drug‐induced BP and highlights the likelihood of these issues becoming increasingly prevalent for the future.